Corporate Diversification and Debt Maturity - Onali, Enrico; Ye, Xiaoxia (Journal of Financial and Quantitative Analysis, 2026)
Abstract We are the first to study the interplay between corporate diversification and debt maturity, both theoretically and empirically. Our models predict that diversification mitigates the debt-overhang problem, making long-term debt more attractive in the presence of rollover costs. Using data on 30,135 firms from 1978 to 2022, we find that multi-division firms have debt maturities at least 1 year longer than stand-alone firms, especially when facing debt overhang. Consistent with our predictions, the excess value of Berger and Ofek (1995) and Mansi and Reeb (2002) increases with debt maturity, suggesting that traditional measures of the diversification discount could be misleading.